Effect on Thermal Conductivity of Concrete Containing Recycled Polyethylene Terephthalate (PET) - Abdul Manaf, Adib Fikri; Shahidan, Shahiron; Mohd Yusof, Norbazlan (International Journal of Sustainable Construction Engineering and Technology, 2024)
The production of plastic solid waste rising annually with the current habit of consumption nowadays prevalent in society. Improper handling of plastic was a significant environmental issue, because it is not readily degradable. There has been considerable debate on the topic of environmental contamination caused by polyethylene terephthalates (PET), and recycling is the best option proposed. Therefore, recycling PET as fiber concrete (FC) in the building industry is one of the viable solutions. A composite material called FC is created by adding fibers to normal concrete. The objective is to define the optimum percentages of PET fiber in concrete and the relationship between the thermal conductivity value (k-value) with density fibers and water absorption of concrete containing PET. The fibers were easily cut from 1.5L mineral water bottles made of PET plastic. Recycled PET fibers have fixed dimensions of 25 mm and 5 mm, respectively. A total of 15 concrete cube samples were tested for 7 and 28 days with measuring 100 mm x 100 mm x 100 mm and with a separate percentage of 0%, 0.5%, 1.0%, 1.5% and 2.0% PET fibers as concrete admixture. The curing process was performed for 7 and 28 days. Using a heat transfer equipment, the samples’ thermal conductivity was evaluated. PET fiber content in concrete gets higher with percentage, which lowers the conductivity of thermal (k value). From the tests conducted, the optimum percentage of PET fibre to produce concrete with lowest thermal conductivity value was 1.0% from concrete weight. Thus, by decreasing heat transfer, building structures may utilize less energy.